Comparative cardiotoxicity risk of pembrolizumab versus nivolumab in cancer patients undergoing immune checkpoint inhibitor therapy: A meta-analysis - Ndjana Lessomo, Fabrice Yves; Wang, Zhiquan; Mukuka, Chishimba (Frontiers in Oncology, 2023)
Objective: Recently several researches reported the incidence of cardiac related toxicities occuring with Nivolumab (opdivo) and Pembrolizumab (Keytruda) . The need for balance between oncology treatment efficacy and reduction of cardiotoxicity effects remains. The objective here was to determine which of pembrolizumab or Nivolumab presents a greater risk of cardiotoxicity reports. Materials and Methods; Meta-analysis was performed using the MOOSE standards, studies were retrieved by searching PUBMED, EMBASE and GOOGLE SCHOLAR, entry terms; Keytruda or Pembrolizumab, PD1 inhibitors, anti-PD1 drugs, and Nivolumab or Opdivo and cardiotoxicities or cardiac toxicity. The study was restricted to original article investigating ICI-induced cardiac irAes. Targeted patients were cancer patients treated with Pembrolizumab or Nivolumab monotherapy, among which, those with records of any cardiac events following the therapy were labelled as events. The measures used for the comparison were the descriptive proportions, probabilities, and odds ratios for meta-analysis. Results: Fifteen studies were included in this meta-analysis, Nivolumab accounted for 55.7% proportions of cardiotoxicity and Pembrolizumab 27.31% the difference was statistically significant P=0.027. The meta-analysis conducted on the Mantel Haenszel method Random effect model yielded a pooled OR=0.73 95%CI [0.43-1.23] P=0.24, with considerable heterogeneity i2=99% P=0, so the difference in cardiotoxicity odds risk between Pembrolizumab and Nivolumab was not statistically significant. On subgroup analysis based on cardiotoxicity type, the “myocarditis” subgroup in which there was no statistical heterogeneity, was associated with a significant cardiotoxicity risk increase with Pembrolizumab OR=1.30[1.07;1.59], P<0.05 i2=0%, Ph=0.4. Conclusion: This is the first meta-analysis addressing a direct comparison between Nivolumab and Pembrolizumab cardiotoxicity potentials. In contrast with previous reports, the overall findings here gave clear illustrations that Nivolumab-induced cardiotoxicities are more reported in the literature over the past years than Pembrolizumab, however, myocarditis would be more likely to occur during the course of Pembrolizumab therapy.